Sarcastic Utterances in the Novel Series Nevermoor - Prastiwi, Umi Denta; Munandar, Aris (Universitas Gadjah Mada, 2024)
This study investigates sarcastic utterances used in the novel series Nevermoor by Jessica Townsend. The novels consist of Nevermoor: The Trials of Morrigan Crow (2017), Wundersmith: The Calling of Morrigan Crow (2018), and Hollowpox: The Hunt for Morrigan Crow (2020). The data for the research were taken from the characters’ dialogues containing sarcastic utterances in the three novels. By applying the descriptive qualitative method, the research aims to classify sarcastic utterances using the theory proposed by Camp (2011): propositional sarcasm, illocutionary sarcasm, lexical sarcasm, and like-prefixed sarcasm. There are 75 data with the four types of sarcastic utterances, including propositional sarcasm (62.67%), illocutionary sarcasm (26.67%), lexical sarcasm (8%), and like-prefixed sarcasm (2.67%). The research also aims to identify negative emotions as triggers for each type of sarcastic utterance using the theory proposed by Vikan (2017): anger, disgust, contempt, sadness, fear, shame, and guilt. The novels contain these negative emotions, except guilt. The type of sarcastic utterance frequently used in the novels is propositional sarcasm. Meanwhile, like-prefixed sarcasm has the most minor occurrence compared to the others. Even though propositional sarcasm and illocutionary sarcasm contain several negative emotions as triggers, lexical sarcasm and like-prefixed sarcasm only have one each.